2021
DOI: 10.1136/bmjresp-2020-000856
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of one time per day, single-inhaler indacaterol/glycopyrronium/mometasone in patients with inadequately controlled asthma: post hoc analysis of IRIDIUM study in Asian population

Abstract: Background and objectiveThe 52-week IRIDIUM study demonstrated the efficacy of indacaterol acetate/glycopyrronium bromide/mometasone furoate (IND/GLY/MF) versus IND/MF and salmeterol xinafoate/fluticasone propionate (SAL/FLU) in patients with symptomatic asthma, despite long-acting β2-agonist/inhaled corticosteroids (LABA/ICS) medium-dose or high-dose, predicted forced expiratory volume in 1 s (FEV1) <80% and at least one exacerbation in the previous year. Here, we present data from a post hoc analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A review of randomized controlled trials evaluating efficacy and safety of add‐on tiotropium in children and adolescents also supports the recently expanded indication by regulatory authorities in patients 6 years or older [51]. The efficacy and safety of fixed‐dose combination (FDC) triple therapy (ICS/LABA/LAMA) for GINA Steps 4 and 5 patients has been demonstrated by the recent clinical trials [52–60]. Therefore, the GINA guidelines have expanded the scope of asthma treatment since 2021 to include other LAMA molecules like glycopyrronium, umeclidinium, and FDC triple therapy for patients with asthma [1, 41, 54, 61, 62].…”
Section: Barriers To Achieving Optimum Asthma Controlmentioning
confidence: 97%
“…A review of randomized controlled trials evaluating efficacy and safety of add‐on tiotropium in children and adolescents also supports the recently expanded indication by regulatory authorities in patients 6 years or older [51]. The efficacy and safety of fixed‐dose combination (FDC) triple therapy (ICS/LABA/LAMA) for GINA Steps 4 and 5 patients has been demonstrated by the recent clinical trials [52–60]. Therefore, the GINA guidelines have expanded the scope of asthma treatment since 2021 to include other LAMA molecules like glycopyrronium, umeclidinium, and FDC triple therapy for patients with asthma [1, 41, 54, 61, 62].…”
Section: Barriers To Achieving Optimum Asthma Controlmentioning
confidence: 97%
“…[ 151 ] Further data showed that this SITT improved lung function, reduced asthma exacerbations, and provided comparable asthma control to the ICS/LABA combination. [ 157 ] SITT with a lower dose of mometasone furoate (mometasone furoate/indacaterol/glycopyrronium 80/150/50 μg) could be considered as an option for a patient with lower biomarkers for type 2 airway inflammation (Evidence D). It can also be considered for step down once control is achieved upon using higher dose SITT.…”
Section: Section 6: Pharmacological Management In Adults and Adolescentsmentioning
confidence: 99%
“…Available triple therapy combinations for asthma management are fluticasone furoate/umeclidinium/vilanterol (Trelegy ® ), Beclomethasone dipropionate/Formoterol/glycopyrronium (Trimbow ® ), and mometasone furoate/glycopyrronium/indacaterol (Enerzair Breezhaler ® ). [ 151 155 156 157 158 ] In a systematic review and meta-analysis, among children (aged 6–18 years) and adults with moderate to severe asthma, triple therapy, compared with dual therapy of medium to high dose ICS/LABA, was significantly associated with 17% fewer severe asthma exacerbations and modest improvements in asthma control without significant differences in quality of life or mortality. [ 503 ] In a meta-analysis of Phase III studies, triple combination therapies with a high-dose ICS/LABA/LAMA administered were more effective than medium-dose FDC against moderate to severe exacerbation and increasing trough FEV 1 .…”
Section: Single Inhaler Triple Therapy With Inhaled Corticosteroids L...mentioning
confidence: 99%
“…1 A triple therapy (inhaled corticosteroid [ICS]/long-acting beta-2 agonist [LABA]/long-acting muscarinic antagonist [LAMA]) is effective for managing moderate-to-severe asthma. [2][3][4][5][6] However, triple therapy is recommended as a second-line treatment for patients with uncontrolled asthma using ICS/LABA dual therapy. 1 The GINA reports also recommend that ICS/LABA dual therapy be selected in patients with uncontrolled asthma using low-dose ICS monotherapy.…”
Section: Introductionmentioning
confidence: 99%